Early Home-Life Antecedents of Children’s Locus of Control - Nowicki, Stephen; Gregory, Steven; Iles-Caven, Yasmin; Ellis, Genette; Golding, Jean (Frontiers in Psychology, 2018)
Children’s external locus of control has been linked to a wide variety of negative academic achievement, personality, and social adjustment outcomes. The purpose of this study was to discover which features of early home environment may facilitate the development of external as opposed to internal control expectancies in children. We use an exposome approach to analyze data from the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort study, a longitudinal study starting in pregnancy in England in 1990-1992. Details of parents and their study children were collected prospectively, and children’s locus of control was assessed at age 8 using an abbreviated form of the most frequently used measure of children’s locus of control (Nowicki-Strickland Internal External locus of control scale). A series of stepwise logistic regression analyses were undertaken to determine the strongest independent associations. The final model (n = 4075 children) comprised 13 variables - those with the strongest associations with the child becoming externally oriented were two that were positive indicators of the mother being distracted (TV on almost the whole time, and a consideration that pets should be treated as members of the family), three that were indicators of protective (negative) effects of interaction between mother and child (child was breast fed, mother read stories to the child, mother cuddled the baby when he/she woke at night), and two divergent indicators of maternal health behavior (more frequent cleaning of the child’s hands before a meal which was associated with a heightened risk of become external, and providing a healthy-type of diet, which was associated with a reduced risk of becoming external). The findings suggest that inadequate early maternal interaction with the child is associated with an increased risk of the child being externally oriented by the age of 8.